Boundary Value Problems for a Class of Sequential Integrodifferential Equations of Fractional Order - Bashir Ahmad; Juan J. Nieto (Journal of Function Spaces and Applications)
We investigate the existence of solutions for a sequential integrodifferential equation of fractional order with some boundary conditions. The existence results are established by means of some standard tools of fixed point theory. An illustrative example is also presented.